2017
DOI: 10.1002/jctb.5313
|View full text |Cite
|
Sign up to set email alerts
|

Tartaric acid and polyphenols recovery from winery waste lees using membrane separation processes

Abstract: BACKGROUND: Wine waste lees are currently partly exploited for tartaric acid (TA) production, through an environment-offensive process, while concurrently occurring bio-active polyphenolic compounds are wasted. This paper, deals with the development of an integrated, environment friendly process, using mild conditions, for recovering TA with simultaneous exploitation of total polyphenols (TPP) from wine lees. RESULTS:A first process step, described in a previous publication, yields a liquid stream containing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…This membrane process was exploited for separation of tartaric acid and polyphenolic compounds recovered from winery waste lees (Kontogiannopoulos et al, 2016). The concentrate, passed through the 1 kDa membrane was polyphenol products with antioxidant activity (EC 50 = 10.0 mg sample/mg DPPH), was obtained for further purification (Kontogiannopoulos, Patsios, Mitrouli, & Karabelas, 2017).…”
Section: Fruit and Beverage Industrymentioning
confidence: 99%
“…This membrane process was exploited for separation of tartaric acid and polyphenolic compounds recovered from winery waste lees (Kontogiannopoulos et al, 2016). The concentrate, passed through the 1 kDa membrane was polyphenol products with antioxidant activity (EC 50 = 10.0 mg sample/mg DPPH), was obtained for further purification (Kontogiannopoulos, Patsios, Mitrouli, & Karabelas, 2017).…”
Section: Fruit and Beverage Industrymentioning
confidence: 99%
“…Furthermore, lees also contain a large amount of bentonite, a natural phyllosilicate clay that is used by wineries to reduce protein instability and precipitate suspended solids responsible for wine turbidity [21]. Usually winemaking lees are re-used for the recovery of tartaric acid [22], but, in recent years, studies showed that the concentration of anthocyanins in these lees are 10 times higher than grape skins [23], and this has increased the interest in these lees. Bentonite slightly bleaches white and red wines absorbing molecules responsible of wines color, such as anthocyanins, tannins, catechins, and polyphenols, which, if properly extracted, can be valorized and used as dyes in DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of membrane technology to obtain various fractions was an efficient strategy to reduce the wastewater organic load and to recover high value phenolic compounds in the three fractions small, medium and large fraction. This type of approach is a cost‐effective and environment‐friendly process which has already been used to recover bioactive polyphenols from other waste streams . The cork industry is of great significance in the western Mediterranean region, with Portugal being the world‐leading producer and exporter.…”
Section: Resultsmentioning
confidence: 99%
“…This type of approach is a cost-effective and environment-friendly process which has already been used to recover bioactive polyphenols from other waste streams. 53 The cork industry is of great significance in the western Mediterranean region, with Portugal being the world-leading producer and exporter. Cork boiling wastewater is a toxic and recalcitrant organic effluent produced by this sector, which constitutes a serious environmental hazard.…”
Section: Resultsmentioning
confidence: 99%